Contribution of “complete response to treatment” to survival in patients with unresectable metastatic colorectal cancer: A retrospective analysis - Gulcan Bulut (Public Library of Science (PLoS), 2021)
Background The aim of the study is to reveal the contribution of complete response (CR) to treatment to overall survival (OS) in patients with unresectable metastatic colorectal cancer. In addition, to evaluate progression-free survival (PFS) in patients who attained CR to treatment and to examine the clinicopathologic features of the patient group with CR. Methods This article is a retrospective chart review. Patients diagnosed with metastatic colorectal cancer were divided into two groups. The systemic treatment was compared with the patients who received a full response according to the Response Evaluation Criteria in Solid Tumors (RECIST1.1) and those who did not attain CR (progression partial response and stable response) in terms of both PFS and OS data, and the effect of attaining CR to treatment on prognosis was evaluated. Results A total of 222 patients were included in the study. 202 of 222 patients could be evaluated in terms of complete response. All data from their files were tabulated and analyzed retrospectively. The mean age of diagnosis of the study group was 60.13 ± 12.52 years. The total number of patients who attained CR to treatment was 31 (15.3%); 171 (84.6%) patients did not attain CR. Patients who had a CR had longer median PFS times than patients who did not have a CR (15.2 vs. 7.4 months, P<0.001). Patients who had CR had longer median survival times than patients who did not have a CR (39.2 vs. 16.9 months, P<0.001). In subgroup patients who underwent primary surgery, the number of patients who attained CR was statistically higher compared with the number of patients who did not attain CR (p<0.001). Complete response was less common in the presence of liver metastasis and bone metastasis (p = 0.041 and p = 0.046, respectively), had a negative prognostic effect. In other words, 89.1% of patients with liver metastasis, 100.0% of patients with bone metastasis, and 88.7% of those who died did not have a CR to the treatment. According to multivariate analysis, CR to treatment, primary surgery, first-line chemotherapy (combination compared with fluoropyrimidine), and no bone metastasis were found to be predictors for OS. Conclusion Providing CR with systemic treatment in patients with unresectable metastatic colorectal cancer (mCRC) contributes to prognosis. The primary resection in our secondary acquisitions from the study, the number of metastatic regions and the combination therapy regimens also contributed to the prognosis.